2022
DOI: 10.1167/iovs.63.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Enriched and Decreased Intestinal Microbes in Active VKH Patients

Abstract: Purpose To determine the possible microbiome related to Vogt–Koyanagi–Harada (VKH) disease in comparison to patients with noninfectious anterior scleritis and healthy people. Methods Fecal samples were extracted from 42 individuals, including 11 patients with active VKH, 11 healthy people, and 20 patients with noninfectious anterior scleritis. We amplified the V3 to V4 16S ribosomal DNA (rDNA) region to obtain the target sequence. Then, the target sequence was amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The changes in both the G and GY groups were significant compared with those in the N group, but the Eggerthella content was higher and the Lachnospiraceae_ND3007_group content lower in the GY group than in the G group. Interestingly, these two microbes also exhibited similar changes between patients with active VKH and patients with scleritis ( Li et al, 2022 ). This result suggests that these two microbes may be nonspecifically involved in various immune-related eye diseases.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The changes in both the G and GY groups were significant compared with those in the N group, but the Eggerthella content was higher and the Lachnospiraceae_ND3007_group content lower in the GY group than in the G group. Interestingly, these two microbes also exhibited similar changes between patients with active VKH and patients with scleritis ( Li et al, 2022 ). This result suggests that these two microbes may be nonspecifically involved in various immune-related eye diseases.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies have shown that a decrease in SCFA levels is closely related to the pathogenesis of RA ( Yang and Cong, 2021 ). Odoribacter ( Turna et al, 2020 ), Roseburia ( Tamanai-Shacoori et al, 2017 ), and Ruminiclostridium_9 ( Hsiao et al, 2021 ) are butyrate producers (butyrate is a type of SCFA); Ruminococcaceae ( Kang et al, 2017 ) and Eubacterium ( Li et al, 2022 ) are short-chain fatty acid (SCFA) producers. In our patients, the abundances of all these microbes were decreased, as was SCFA production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations